Psychological factors and genetic characteristics of rural cannabis users - Lachowicz, Milena; Chmielowiec, Jolanta; Chmielowiec, Krzysztof; Suchanecka, Aleksandra; Michałowska-Sawczyn, Monika; Mierzecki, Artur; Mroczek, Bożena; Grzywacz, Anna (Annals of Agricultural and Environmental Medicine, 2020)
Marijuana is one of the most widely used psychoactive substance. There is evidence of genetic predisposition for addiction. The aim of the study is to evaluate personality traits measured by the NEO Five-Factor Inventory and State-Trait Anxiety Inventory, combined with analysis of rs1079597 and rs1800498 located in the gene. The study group consisted of 214 rural cannabinoid users and 301 controls. The same psychometric test and real-time PCR genotyping were performed in both studied groups. The values of Anxiety state, Anxiety trait, NEO FFI: Neuroticism and Openness in the rural cannabis using group were significantly higher than in the control group. On the other hand, lower values were observed among rural people using cannabis compared to the control group for NEO FFI: Extraversion, Agreeability and Conscientiousness. In the Anxiety trait subscale, a 2% association with the polymorphism rs1079597 was detected in subjects using cannabis. However, for the rs1800498, there was no effect on the differences in personality traits between rural cannabis users and the control group. The study shows differences in personality traits between the cannabis using group and controls. Interaction between genetic factors and personality traits was also detected. The association showing the combination of psychological characteristics and genetic variants can bring us closer to the overall picture of the issue of marijuana addiction.